CAM18sl brightness prediction for unrelated saturated stimuli including age effects - Preciado Olvera, Oscar Ulises (2021)
Modelling the influence of age on the perception of brightness of visual stimuli is an important topic for indoor and outdoor lighting. As people get older, the transmittance of the ocular media becomes lower, especially in the blue wavelength region. This paper reports on an experimental study aiming to evaluate how the brightness perception of red and blue stimuli is affected by the age of the observer. A matching experiment has been set up in which both young (25 years old on average) and older (70 years old on average) adult observers had to match the brightness of a blue stimulus with the brightness of a red stimulus, both surrounded by a dark background (unrelated stimuli). A significant difference in brightness perception between the two groups of observers was found. In particular, older people report a decrease in brightness perception for the blue stimuli compared to younger people. The results show that the brightness correlate of the colour appearance model CAM18sl (applied with zero luminance background) adequately predicts the matching results of young observers, but failed to predict the results obtained by the older observers. As CAM18sl is built on cone fundamentals which include the transmittance of the ocular media and consider the age of the observer as an input parameter, the authors developed the idea to substitute the cone fundamentals for a young observer by the cone fundamentals for a 70 years old observer. This updated CAM18sl performed very well for the older observer as well, on condition that the transmittance of the ocular media is isolated and kept out of the normalization of the cone fundamentals.